Reliable expression of ChR2-EYFP and ChrimsonR-tdTomato in PV cells. - Lilia Kukovska (22683586) (2025)
A) Example confocal fluorescence imaging region in primary visual cortex of PV-cre::Ai32 mice showing expression of ChR2-EYFP (left) at cell membrane of PV cells (right). B) Percentage of PV cells with expression of ChR2-EYFP at the cell membrane in three mice. The percentage was similar across mice: mouse 1 = 96.72% (N = 61), mouse 2 = 95.15% (N = 62), mouse 3 = 95.56% (N = 45). C) Example confocal fluorescence imaging region in primary visual cortex of PV-cre mouse at injection site, showing expression of ChrimsonR-tdTomato (left) at cell membrane of PV cells (right). D) Percentage of PV cells with expression of ChrimsonR-tdTomato at the cell membrane in three mice. The percentage was similar across mice: mouse 1 = 97.44% (N = 39), mouse 2 = 98.46% (N = 65), mouse 3 = 93.33% (N = 30). White arrows indicate identified PV cells. E) Confocal microscope image (2.5x objective) of coronal slice showing GCaMP (green) and ChrimsonR (red) overlaid on DAPI stain (blue) showing labeling in V1 across cortical layers 1–6 (with injections at 200 and 400 micrometer). F) Example confocal image of horizontal slice showing GCaMP (green) and ChrimsonR (red) fluorescence. Full width at half maximum (FWHM) estimates of spread of fluorescence were similar for GCaMP (median 974 micrometer, 738–1,028, N = 5) and ChrimsonR median (763, 733–1,010, N = 5). G) Example zoomed out in-vivo two-photon microscope image (imaging of neuronal activity was done with increased zoom). Labeled cell bodies were contained within area of ~800 micrometer (N = 4 examples). (TIFF)